Vaginal biogenic amines: biomarkers of bacterial vaginosis or precursors to vaginal dysbiosis? - Nelson, Tiffanie M.; Borgogna, Joanna-Lynn C.; Brotman, Rebecca M.; Ravel, Jacques; Walk, Seth T.; Yeoman, Carl J. (Frontiers in Physiology, 2015)
Bacterial vaginosis (BV) is the most common vaginal disorder among reproductive age women. One clinical indicator of BV is a ‘fishy’ odor. This odor has been associated with increases in several biogenic amines (BAs) that may serve as important biomarkers. Within the vagina, BA production has been linked to various vaginal taxa, yet their genetic capability to synthesize BAs is unknown. Using a bioinformatics approach, we show that relatively few vaginal taxa are predicted to be capable of producing BAs. Many of these taxa (Dialister, Prevotella, Parvimonas, Megasphaera, Peptostreptococcus, and Veillonella spp.) are more abundant in the vaginal microbial community state type (CST) IV, which is depleted in lactobacilli. Several of the major Lactobacillus species (L. crispatus, L. jensenii, and L. gasseri) were identified as possessing gene sequences for proteins predicted to be capable of putrescine production. Finally, we show in a small cross sectional study of 37 women that the BAs putrescine, cadaverine and tyramine are significantly higher in CST IV over CSTs I and III. These data support the hypothesis that BA production is conducted by few vaginal taxa and may be important to the outgrowth of BV-associated (vaginal dysbiosis) vaginal bacteria.